Financial market instruments in the process of financing small and medium-sized businesses - Wang Xiaoting (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the process of forming a portfolio of securities as an effective way of making investments. The subject of research is the theoretical and methodological principles of forming a portfolio of securities as an effective way of making investments. The purpose of the qualifying master's thesis is to generalize the theoretical and methodological principles of forming a portfolio of securities as an effective way of making investments and to develop practical recommendations for its improvement in modern business conditions. Based on the results of the research, theoretical and methodological approaches, as well as practical recommendations, are formulated for improving the process of forming a portfolio of securities as an effective way of making investments. The obtained results can be used for forming an optimal portfolio of securities in the practical activities of the National Commission for Securities and the Stock Market of Ukraine, the Ukrainian Association of Investment Business, and Ukrainian securities issuers.
Інструменти фінансового ринку у процесі фінансування малого та середнього бізнесу
Scientific adviser: Oriekhova Kateryna, PhD in economics, associate professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Economics; securities; stock market; investments; investment portfolio; world experience; financial literacy; self-regulatory organization